India’s Inclusion in the Customs Union: Understanding the Challenges in the Framework of New Delhi’s Policy towards Central Asia - ORAKBAYEVA, Ulbolsyn; MEDEUBAYEVA, Zhanar; ORAKBAYEV, Yerlan (Journal of Advanced Research in Law and Economics; Vol 6 No 2 (2015): JARLE Volume VI Issue 2(12) Summer 2015, 2016)
This paper suggests that India’s recent attempt to join the Custom Union would support closer ties with Central Asia. Since the collapse of the USSR, India has been developing steadily and rapidly and has expanded its geopolitical interests in the Central Asian region. It is seeking for new routes of oil and gas delivery. In 2013, Indian authorities proposed to join Free Trade Zone with Russia, Kazakhstan and Belarus. The author considers this proposal as a part of India’s general policy towards Central Asia. This paper deals initially with the issue of India’s membership in the Custom union, and then focuses on the gains for Union members. This study utilizes a comparative method and statistical analysis for supporting arguments. The author argues that the Custom Union could be the basis for closer cooperation between India and Russia as well as between India and Central Asia. As more Central Asian states join this Union, Indian commercial links with the region will grow even further.
Keywords: India, Central Asia, Russia, New Great Game, Customs Union, Connect Central Asia Policy